Analyzing factors influencing SME readiness for smart retail: A structural equation model approach - Kantaphon Phanitrat; Wilert Puriwat; Danupol Hoonsopon (Problems and Perspectives in Management)
The objective of this study is to explore factors influencing the readiness to enter smart retail businesses. This paper employed a quantitative approach. The sample consisted of 323 retail entrepreneurs in Thailand. Data were collected through questionnaires and analyzed using structural equation modeling (SEM) to verify whether the model constructed in this analysis is consistent, coherent, and suitable for practical application. The influencing factors are as follows: 1) The acceptance and use of technology by entrepreneurs (β = 0.63, p < 0.05), 2) The resource base of entrepreneurs (β = 0.52, p < 0.05), 3) The aspect of business networking by entrepreneurs (β = 0.48, p < 0.05), and 4) The competencies of entrepreneurs (β = 0.40, p < 0.05). These factors significantly affect the readiness to enter the retail market, aligning with empirical data. The structural equation model analysis examines the factors influencing the readiness of small and medium enterprise operators to enter the retail trade. The model meets the specified criteria, as indicated by the following compliance indices: CMIN/df = 2.841, CFI = 0.945, IFI = 0.942, and RMR = 0.036. AcknowledgmentGratitude is expressed to all the faculty members of the Doctor of Philosophy Program in Technopreneurship and Innovation Management at Chulalongkorn University for imparting valuable knowledge and experience, as well as for their support and encouragement.